Inguinal hernia common problem of modern surgery - Tobiasz, Michał; Turkosz, Agnieszka; Tobiasz, Maciej; Polski, Paweł; Wójcik, Rafał (Journal of Education, Health and Sport, 2019)
Hernia is a very common challenge faced by modern medicine. It is estimated that this problem affects about 20 million people annually, including 30% abdominal hernias with the highest percentage of inguinal hernias. Despite constant progress of imaging methods, surgical techniques and understanding of the biomechanics muscles, it is still a serious challenge for physicians. This article deals with the most important issues related to the diagnosis and treatment of inguinal hernia. We pay particular attention to the frequency of complications after surgery, comparing the effectiveness of specific repair methods.